Corporate governance after the financial crisis - Bainbridge, Stephen M. (New York : Oxford University Press, 2012)
Traditionally, corporate law was the province of the states. Today, however, the federal government is increasingly engaged in corporate governance regulation. The changes examined in this work provide a series of case studies in which to explore the question of whether federalization will lead to better outcomes.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Corporate governance -- Law and legislation -- United States; Global Financial Crisis, 2008-2009.